Ethnic variation in stunting and its concomitant factors among indigenous preschool children of Purulia district, West Bengal, India - Gope, Shiule (2025)
This study aimed to investigate variations in the prevalence of stunting by age, sex, and ethnicity, as well as its associated factors. The present cross-sectional study was conducted in three blocks of Purulia district, focusing on children from two distinct ethnic groups (Kurmi and Sabar). A total of 701 study participants (boys: 372; girls: 329) were investigated, from the Kurmi (377) and Sabar (324) communities, within the age group of 1–5 years. The children’s stunting status was assessed in terms of height using WHO-recommended Z-score values. The overall rate of stunting was 58.2%, with the Sabar children (75%) having a significantly higher rate of stunting than the Kurmi ones (43.77%) (χ2 = 69.87, p < .001). A significant association was also observed between the prevalence of stunting and socio-behavioural variables. Binary logistic regression analysis revealed that birth weight (BW) was a significant predictor of stunting among Kurmi boys (Wald = 16.08, p < .001). Colostrum feeding status (CFS) was also a significantly strong predictor of stunting, irrespective of sex, among the Kurmi children (Wald = 18.56, p < .001). Number of sibs (NS) (Wald = 9.75, p < .001) was a predictor among the studied children; more specifically, it was a predictor among Kurmi girls (Wald = 7.71, p < .05). Similarly, among the Sabar children, birth order (BO) was found to be a significant predictor of stunting (Wald = 8.71, p < .01). Furthermore, it was found that ethnicity (Wald = 37.96, p < .001) was the strongest predictor of stunting after controlling for the effects of all other socio-behavioral variables. The study revealed ethnic variation in the impact of socio-behavioral determinants on stunting status among the studied children, with different socio-demographic and behavioral characteristics serving as significant predictors of stunting.